Cover Jurnal Fitopatologi Vol. 19 No. 4, Juli 2023 - Editors Jurnal Fitopatologi Indonesia (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2023)
This editorial contains the front cover, editorial page, and back cover of the Jurnal Fitopatologi Indonesia Vol. 19 No. 4, July 2023